Netwerk Galerij : Handleiding 01-02. - Danckaert, Bert; Evermore, Alice; Peeters, Wim; Snyders, Frank; Vermeiren, Gerrit (Aalst : Netwerk Galerij Aalst, 2002)
Augustynen, Ellen ; De Boe, Rik ; Burght, Chris Van der ; De Decker, Koen ; Evermore, Alice ; De Gendt, Greet ; Geurts, Frederic ; Goiris, Geert ; HAP ; Jessen, Joseph ; Marcasiano, Colombe ; Morrens, Peter ; Moulin, Nicolas ; van Nes, Boris ; Paulus, Stephanie ; Renneboog, Lucie ; Vermeulen, Angelo ; Zoete, Dirk
biog., tent. p. 73-77
Dit boek bevat beschouwingen over de tentoonstellingen van de periode 2001 en 2002
Engels & Nederlands
boek